(untitled) (Alternautas, 2022)
The 1950s were a decade full of aspirations and struggles all over the globe and in a specific way for Latin America. Excluded from the vision of the West and Western infrastructure, such as NATO, while also not part of the socialist bloc, the so-called second world, Latin America was trying to come to grips with its place in the world. This paper will trace the shift in political economic thought in the 1950s, explaining how cepalismo played a central role in defining underdevelopment, at a time when the idea of a Third World was still in its infancy.